Radiometric properties of sepiolite minerals from quarries in central Anatolia of Turkey - Hancerliogullari Aybaba; Ali Madee Yosef G.; Kurnaz Ash; Turhan Seref (National Library of Serbia, 2019)
Sepiolite is a naturally occurring clay mineral of sedimentary origin and is a magnesium hydrosilicate. Sepiolite has been widely used as an additive raw material in ceramics and cement industry, pharmaceutical, cleaning-detergent, paper, paint, cosmetic agriculture, fertilizer, etc. In this study, the natural radioactivity levels, radon emanation coefficients and radon exhalation rates of 30 sepiolite samples collected from open three sepiolite quarries (Beylikova, Polath and Sivrihisar) in Central Anatolia region of Turkey were determined by using a gamma-ray spectrometry with an HPGe detector. The average absorbed gamma dose rates directly measured in Beylikova, Polath and Sivrihisar open three sepiolite quarries located in Central Anatolia region of Turkey were found as 59, 65, and 64 nGyh?1, respectively. The average activity concentrations of 226Ra, 232Th, and 40K in 30 sepiolite samples collected from those quarries were found as 38.6, 12.4, and 67.4 Bqkg?1, respectively. The average emanation coefficient and exhalation rate of radon of sepiolite samples were determined as 22 % and 0.065 Bqkg?1h?1, respectively. Also, radiological parameters (outdoor absorbed gamma dose rate, annual effective dose rate, external and internal index) were estimated to evaluate the use of sepiolite samples as additive raw materials in the building sector.
Keywords: radon emanation coefficient; gamma-ray spectrometry; sepiolite; Nuclear and particle physics. Atomic energy. Radioactivity; natural radioactivity; radon mass exhalation rate; QC770-798; outdoor absorbed gamma dose rate